ANALYSIS OF STUDENTS’ WRITING DESCRIPTIVE TEXT BY USING PROOFREADER AT THE GRADE X OF SMA NEGERI 1 PORTIBI - Romintan, Serli (CV. Alfa Pustaka, 2023)
The aims of this research are to find out the types of error and dominant error in students’ writing Descriptive Text by using Proofreader as analysis tool, at the grade X of SMA Negeri 1 Portibi. The researcher used purposive random sampling at the grade X IPA 1 with the number of sample were 33 students. The result showed that types of errors made by students in writing Descriptive Text were; spelling(27,8%), style(10,1%), punctuation(3,7%), grammar(7,3%), capitalization(32,7%), collocation(1,1%), typography(9,9%), redundant phrase(2,1%), and miscellaneous(4,9%). The dominant errors in students’ writing Descriptive Text were; capitalization in the highest percentage that is 32,7% with total error 139, and followed by spelling(118), style(43), typography(42), grammar(31), miscellaneous(21), punctuation(16), redundant phrase(9), and collocation(5)